2011
DOI: 10.1109/tvt.2011.2110664
|View full text |Cite
|
Sign up to set email alerts
|

Preamble Design Using Embedded Signaling for OFDM Broadcast Systems Based on Reduced-Complexity Distance Detection

Abstract: Abstract-The second-generation digital terrestrial television broadcasting standard adopts the so-called P1 symbol as the preamble for initial synchronization. The P1 symbol also carries a number of basic transmission parameters, including the fast Fourier transform size and the single-input/single-output as well as multiple-input/single-output mode, to appropriately configure the receiver for carrying out the subsequent processing. In this paper, an improved preamble design is proposed, where a pair of traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This section evaluates the performance of the proposed preamble compared with two conventional preambles for DVB-T2 [2] and DTMB-A [4], respectively. Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This section evaluates the performance of the proposed preamble compared with two conventional preambles for DVB-T2 [2] and DTMB-A [4], respectively. Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Fig. 7 compares the signaling error rate (SER) of the proposed preamble with that of two conventional preambles over two dispersive channels (Brazil-B [4] and typical urban TU-6 [2, pp.174-175] channel models). It can be observed that the proposed preamble outperforms the preamble for DTMB-A and the s 1 signaling for DVB-T2, and achieves very similar performance as the s 2 signaling for DVB-T2 over both dispersive channels.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations